Regimes de verdade em territórios surdos: mídias sociais como dispositivos biopolíticos nos processos de subjetivação de vidas surdas - Conceição-de Andrade, Bianca Salles (2022)
The Brazilian Sign Language - Libras has steadily gained notoriety in society, marking important milestones. Among them, we can highlight laws, decrees, social movements, and rights the deaf communities conquered by means of resistance. Social media has increased the visibility of deaf people and Libras, accelerating the dissemination of information. In the current federal government (2019-2022), the first lady's advocacy of the deaf communities remains as an emblem for the campaign and the social acts of the government. Therefore, the volume of publicity of materials available in the (digital and television) media in sign language has increased. However, crucial issues, such as bilingual education and professionalization of translators and interpreters, has not been looked at. On the other hand, they have been labelled as volunteer work. In this sense, we support this thesis as: the social recognition of Libras and its presence in social media extended the linguistic right and the presence of the deaf in society. At the same time, it produced three regimes of truth (conservative, progressive and publicized). They are the founding basis for the processes of subjectivation of deaf lives and of their territories anchored by biopolitics. Therefore, the objective of the research was to problematize the production process of these three regimes of truth. These regimes are socially dispersed and potentiate the processes of subjectivation of deaf lives from the effects of biopolitical media devices, which engulf Libras and the deaf in the contemporary neoliberal context. I adopt the philosophies of difference to support the research. The regimes of truth, developed by Michel Foucault, and the processes of subjectivation in an encounter between Félix Guattari and Michel Foucault were selected as tool concepts. Principles of Michel Foucault's anarchaeological methodology underpins this research. Two data collections were conducted: 1) the selection of videos in social media that have the potential to function as biopolitical devices and 2) semi-structured interviews with ten questions and four participants, necessarily deaf, signers and of legal age, on these same videos. All interviews were recorded and conducted in Libras remotely. Finally, the answers were translated from Libras into Portuguese. The analyzes were based on three construction axes, namely: 1) conservative truth regimes, 2) progressive truth regimes and 3) publicized truth regimes. From the triangulation between these analytical axes, bringing points about the selected social media and the speeches of the participants, we argue that Libras has been an agency device of these three regimes of truth. However, we also affirm that, even in capturing the deaf movement for the production of conservative speeches aligned with neoliberalism, there are always spaces for resistance in other forms of production of subjectivation processes, in a more active force. Hopefully, this thesis can contribute to advances in the field of deaf studies, as well as bring actions to the field of education and reflective-active practices for more plural forms of the processes of subjectivation of deaf lives.